Acidic Electrolyzed Water Inhibits the Viability of Gardnerella spp. via Oxidative Stress Response - Zhao, Chongyu; Chen, Yu; Gao, Lvfen; Huang, Jue; Yang, Xiurou; Pei, Luowei; Ye, Zhangying; Zhu, Linyan (Frontiers in Medicine, 2022)
The vaginal microbiota, dominated by Lactobacilli, plays an important role in maintaining women’s health. Disturbance of the vaginal microbiota allows infection by various pathogens such as Gardnerella spp (GS) and related anaerobic bacteria resulting in bacterial vaginosis (BV). At present, the treatment options for BV are extremely limited. Treatment of antibacterial drugs and vaginal acidification are the two primary therapeutic methods. Acid electrolyzed water (AEW) is known to inactivate microorganisms and is considered a medical application in recent years. Studies have found that Lactobacillus acidophilus (LA) probiotics helps to inhibit GS induced BV. Our study took Gardnerella spp (GS) and Lactobacillus acidophilus (LA) as the research object, aiming to explore AEW as a potential alternative therapy for BV and its underlying mechanisms. We first obtained the pH of AEW (3.71-4.22) close to normal vaginal pH (3.8-4.5) to maintain normal vaginal acidification conditions. Plate counting experiments showed that AEW (pH:4.07, ORP:890.67, ACC: 20 ppm) AEW (20 ppm) could better inhibit the viability of GS but had a more negligible effect on LA. Then we preliminarily explored the possible mechanism of AEW anti-GS by using cell biology experiments and transmission electron microscopy. Results showed that the membrane permeability significantly was increased and the integrity of cell membrane was destroyed by AEW in GS than those in LA. AEW also caused protein leakage and cell lysis in GS without affecting LA. Meanwhile, AEW induced a number of reactive oxygen species (ROS) production in GS, with no obvious LA changes. Finally, we found that 20ppm AEW exhibited excellent antibacterial effect on the vaginal secretions of women diagnosed with BV by Amsel criteria and sialic acid plum method. Taken together, our findings manifest that 20ppm AEW has an excellent antibacterial effect in GS with little effect on LA, which might be expected to become a potential therapy for BV.